Vplivi zdravil na rezultate laboratorijskih preiskav - Jerin, Aleš (Medicinski razgledi, 1998)
Unexpected results of laboratory tests may be due to various factors. These include drug effects, which may be either biological, or due to analytical interferences. The more common biological effects include direct and indirect effect produced by drugs in vivo; in consequence laboratory tests yield unexpected, yet correct results. By contrast, the results of tests influenced by the interference of drugs with analytical techniques are not accurate. International guideleines for the evaluation of drug effects have been formulated, allowing for the comparbility of data of different studies. The development of drug effects databases has facilitated the acces to the rapidly increasing body of data, which need to be evaluated for their clinical and laboratory significance.
Keywords: diagnostika; drug; zdravila; laboratorijske preiskave; vplivi